En snusfornuftig afhandling om Origenes’ kristologi og soteriologi - Petersen, Anders Klostergaard (Dansk Teologisk Tidsskrift, 2015)
In the context of Danish studies of Origen, Anders-Christian Jacobsen’s thesis for the attainment of the higher doctoral degree marks a significant event. It is the first comprehensive Danish work on Origen since Hal Koch’s Pronoia und Paideusis (1932). Yet, the thesis promises more than it can accomplish. I criticise the book for falling short on two accounts. First, throughout the book there is a continuous self-claimed conflation of Origen’s use of allegorisation with Jacobsen’ method, since he advocates the view that in order to grasp Origen one has to adopt his method. Second, by focusing narrowly on works pertaining to the discussion of Origen’s Christology and soteriology the author eclipses that scholarly trajectory which during the last forty years has provided significant insight into Origen’s epistemology. The question is never posed whether the asserted unity of the Christology is a reflection of the underlying Platonic epistemology or vice-versa. Finally, Jacobsen emphasises how his thesis provides a methodological novum by introducing a clear-cut distinction between the addressees of Origen’s Homilies (‘simple Christians’) and the recipients of his Biblical Commentaries (‘spiritually mature Christians’). Yet, this distinction originates in Karen Jo Torjesen’s Hermeneutical Procedure and Theological Method in Origen’s Exegesis (Berlin and New York, DeGruyter 1986, p. 61).